PEMBUATAN BRIKET ARANG DARI SERBUK KAYU SEBAGAI SUMBER ENERGI ALTERNATIF - Anis Masyruroh; Iroh Rahmawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Briquette is an alternative energy substitute for fuel produced from underutilized organic materials or biomass. Several types of biomass waste have considerable potentials such as wood waste, rice husks, straw, bagasse, and palm shells. In this paper, the results of the manufacture of charcoal briquettes from sawdust are presented. The writing process is carried out using a modified drum furnace. The charcoal obtained is then ground to a powder form and then filtered using a 40 mesh sieve. The charcoal that passes the filter is then mixed with 5% tapioca flour adhesive. The raw material is printed with a paragon mold, then dried in the sun for 1 to 3 days depending on weather conditions. Charcoal briquettes produced in general can produce better physical and chemical properties when compared to the quality of the raw materials. Moisture content ranged from 2.59 - 9.31%, ash content 1.75 - 10.47%, volatile matter content 13.45 - 19.89%, bound carbon content 67.17 - 75.75%, density 0 .32 - 0.71 g/cm2, compressive strength 6.57 - 18.19 kg/cm3, and the calorific value ranged from 5.953 to 6.906 ka/g. Seeing from the results of this study that sawdust from the frame industry waste can be used as an alternative raw material in the manufacture of briquettes